The effects of information and naming restriction on South African consumer preferences for farm-raised meat and meat alternatives - Rejoice Tobias-Mamina; Yolanda Jordaan; Lin Lin; David L. Ortega (Future Foods, 2025)
High meat consumption in South Africa is driven by population growth, increased income, and urbanization. However, high meat production raises environmental and societal concerns, highlighting the need to shift toward more sustainable protein sources to reduce these impacts. This study examines consumer preferences for plant-based, insect-based, and cultured meat as alternatives, alongside the effects of environmental and health information and naming restrictions on these preferences. A food choice experiment was administered on 1013 urban South African food shoppers to assess preferences for three alternative burger patties relative to farm-raised beef patties. Respondents were randomly assigned to treatments varying by health, environmental, and product naming information. Results indicate that farm-raised beef captures approximately 96 % of the market share within our sample of urban food shoppers. Naming restrictions do not significantly affect beef demand but increase the market share for plant-based and cultured alternatives. Health information leads to slightly higher preferences for plant-based options than environmental information. Preference for insect-based alternatives remains low, likely due to an aversion to insects. These findings enhance understanding of consumer preferences for alternative meat products and naming restrictions, informing policies aimed at reducing the environmental and societal impacts of livestock production in South Africa.